Posyandu Model for Children Based on Stimulus Growth using the UCIL Method Influences on the Level of Mother's Knowledge - Taukhit Taukhit; Rudi Haryono (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
One of the problems with children's health is the relatively high development delay. The delay in child development is influenced by the growth and development stimulus of the parent's child. Efforts to reduce child developmental disorders can be increased through the Posyandu program. The existing Posyandu needs to be remodeling so that it can be an approach to optimizing children's growth and development. The approach to optimizing the achievement of child development tasks through the Posyandu program that emphasizes UCIL activities is expected to be one way to overcome the problem of delayed child development. The purpose of this study was to determine the effect of the growth and development stimulus-based posyandu for toddlers with the UCIL method on increasing maternal knowledge in child development. This study used a quasi-experimental design in the form of a pretest - post test intervention with a control group. The study population was mothers with toddlers who actively attended Posyandu. The sample consisted of 20 respondents for the intervention group and 20 respondents for the control group. The sampling technique was purposive sampling. The data was collected by measuring the pre-test and post-test after implementing the model. The data analysis used paired t-test to determine the effect of the intervention on the intervention group and independent t-test to see the differences between the effects between groups. The results showed that there was an effect of Posyandu for Toddlers based on the Growth and Development Stimulus with the UCIL Model on the level of knowledge of mothers in child development with a value of p = 0.000 (significant, p value <0.05).